PENINGKATAN HASIL BELAJAR SISWA MELALUI PENDEKATAN STEAM (SCIENCE, TECHNOLOGY, ENGINERRING, ART, MATHEMATIC) PADA MATA PELAJARAN IPA SISWA KELAS III SD NEGERI 122/V PARIT LAPIS - Aini, Nur; Indryani; Ugi Nugraha; Urip Sulistiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to improve the science learning outcomes of class III students at SD Negeri 122/V Parit Lapis in semester 1 of the 2024/2025 academic year through implementing the STEAM learning approach. The research was carried out over a period of one month from October 2024 to November 2024. The subjects of this classroom action research were 26 class III students at SD Negeri 122/V Parit Lapis. Class III consists of 11 female students and 15 male students. This classroom action research uses the Kemmis and Mc Taggart model which is carried out in 2 cycles, each consisting of four research stages, namely planning, implementation, observation and reflection. The data analysis carried out included qualitative analysis and quantitative analysis. Qualitative analysis was carried out by describing in words the results obtained in cycle I and cycle II. Quantitative data analysis is presented in the form of numbers from the results of observational assessments of student and teacher activities and learning outcomes which were compared in cycle I and cycle II which were then used to make improvements/reflections. The research results show that using the STEAM approach can improve science learning outcomes for class III students at SD Negeri 122/V Parit Lapis. This can be seen from the results obtained in cycle I to cycle II which saw an increase in the percentage of student completion. In the first cycle, 20 students got a complete score, with 6 students not completing and the percentage of complete learning results was 77%. In cycle II there was an increase to 24 students getting a pass mark and 2 students did not finish with a percentage of 92.3% with an increase of 15.3%.